Volume 6: Polar and Arctic Sciences and Technology; Offshore Geotechnics; Petroleum Technology Symposium 2013
DOI: 10.1115/omae2013-10589
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate Rock Type Matrix RocMat, The Ultimate Rock Properties Catalogue

Abstract: Rock typing is one of the most important steps in reservoir modeling, and it’s the main task in reservoir characterization. In carbonate, the rock typing work that’s been performed during the last two decades had a little progress in term of providing reliable estimation of reservoir behavior. However, the development of Conjunction Rock Properties Convergence, CROPC, a carbonate rock typing concept that provided an important and easy solution to the carbonate rock typing gaps, has a major breakthrough, even t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The geoscientist starts by analyzing the objectives. This research's objective targets supervised semantic segmentation of the rock uCT images with utmost accuracy and efficiency [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Then the geoscientist identifies the input data type that provides the bases for understanding the objective set and then chooses the suitable algorithms, based on accurate sets, that deliver the highest accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…The geoscientist starts by analyzing the objectives. This research's objective targets supervised semantic segmentation of the rock uCT images with utmost accuracy and efficiency [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Then the geoscientist identifies the input data type that provides the bases for understanding the objective set and then chooses the suitable algorithms, based on accurate sets, that deliver the highest accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…The choice of the machine learning algorithm is critical, because heterogeneous embeds complex interlinks within its features. Our heterogeneous system is Cretaceous carbonate rock fabric [4][5][6][7][8][9][10][11][12][13] where we target digitally classifying [14] it based on its physical and chemical properties using machine learning. The literature suggested that a decision tree-based algorithm performs better [15] than an artificial neural network-based algorithm, like Convolutional Neural Network (CNN), that works better with homogeneous systems [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Each 3D geological grid block [1][2][3] requires a rock type [4][5][6][7][8] with physical and chemical properties [9,10] like lithology [11,12], porosity, permeability, capillary pressure [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], fluid saturation [31][32][33][34][35][36][37][38][39], relative permeability [40], and wettability [41,42]. Wettability is one of the main controlling attributes of fluid flow in porous media.…”
Section: Introductionmentioning
confidence: 99%